Awareness about human papilloma virus vaccine among medical students - Kamini, Snigdha; Bhimarasetty, Devi Madhavi (Asian Journal of Medical Sciences, 2016)
Background: Human papilloma virus is a causative agent of cervical cancer. Hence,vaccination against HPV is an important mode of primary prevention against cervical cancer. Two vaccines against HPV have been approved and recommended for use in India. However the availability of these vaccines is hardly known and seldom utilised even among the medical fraternity. Aims and Objectives: This study aims to find out the awareness about HPV vaccination among medical students of Andhra Medical College, India. Results of this study will help in assessing the need for awareness programs among health care professionals regarding this important public health issue. Materials and Methods: An observational descriptive study was conducted to know the awareness of HPV infection and vaccination among medical students of a government medical college at Visakhapatnam in Andhra Pradesh. A pretested questionnaire was administered to students of final MBBS Part 1 and final MBBS part 2. Results were analyzed in MS excel and the statistical significance of difference in knowledge between males and females was assessed. Results: Overall, the level of awareness reported was 54.5%. Females had slightly better knowledge than males. Students of final year Part 2 had better knowledge the Final year part 1. The most commonly cited source of information was medical education and the most important factor that deterred subjects from receiving/advising HPV vaccination was lack of knowledge. Conclusion: There exists a large gap in knowledge regarding HPV vaccination. Addressing this gap is necessary if we want to decrease the burden of cervical cancer in India. Medical students, health care providers should be sensitized first and then we should reach out to the public. Asian Journal of Medical Sciences Vol.7(4) 2016 64-67